Why do Banks Disappear? The Determinants of U.S. Bank Failures and Acquisitions - Wheelock, David C.; Wilson, Paul W. (The Review of Economics and Statistics, 2000)
This paper seeks to identify the characteristics that make individual U.S. banks more likely to fail or be acquired. We use bank-specific information to estimate competing-risks hazard models with time-varying covariates. We use alternative measures of productive efficiency to proxy management quality, and find that inefficiency increases the risk of failure while reducing the probability of a bank's being acquired. Finally, we show that the closer to insolvency a bank is (as reflected by a low equity-to-assets ratio) the more likely is its acquisition.